2011
DOI: 10.1109/tvlsi.2010.2077315
|View full text |Cite
|
Sign up to set email alerts
|

Gate Leakage Impact on Full Open Defects in Interconnect Lines

Abstract: Abstract-An

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The faulty line voltage depends on the surroundings, the capacitances of the driven gates, and on the initial trapped charge, as reported in previous works [4]- [12]. Furthermore, it has been recently Manuscript demonstrated that gate leakage currents also affect the behavior of faulty lines due to interconnect full open defects in nanometer technologies [13]- [16]. The logic interpretation of the faulty line due to an interconnect open depends on the logic input threshold voltages of the downstream gates for each particular test pattern.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The faulty line voltage depends on the surroundings, the capacitances of the driven gates, and on the initial trapped charge, as reported in previous works [4]- [12]. Furthermore, it has been recently Manuscript demonstrated that gate leakage currents also affect the behavior of faulty lines due to interconnect full open defects in nanometer technologies [13]- [16]. The logic interpretation of the faulty line due to an interconnect open depends on the logic input threshold voltages of the downstream gates for each particular test pattern.…”
Section: Introductionmentioning
confidence: 59%
“…The points represent the voltage difference due to the influence of gate leakage currents between two consecutive patterns (including the scan vectors). The dotted lines correspond to the predicted B IG(VDD) and B IG(GND) bounds according to the simplified expressions (15) and (16). It is observed how B IG(VDD) and B IG (GND) act, in fact, as a lower and a upper bound, respectively.…”
Section: F Simplification Of Gate Leakage Charge Bounds Computationmentioning
confidence: 94%
See 1 more Smart Citation
“…The exact influence depends on the relationship between the capacitances undergoing a rising (falling) transition or remaining at a constant value. The faulty node behaves similar to an interconnect line affected by a full open [22]- [25]. The difference lies in that the faulty node is in a high impedance state for some specific excitations whereas the interconnect line affected by a full open always remains disconnected from the driver.…”
Section: B Influence Of Downstream Parasitic Capacitancesmentioning
confidence: 99%
“…The electrical behavior of the floating node is determined by the neighborhood capacitances to the defective floating node, the transistor gate charge, and the charges trapped at the floating line [4]- [6]. Recently, it has been found that the gate tunneling leakage may influence the interconnect open behavior in some technologies [7], but this effect is not considered in this brief. Manuscript Detectability conditions as well as test generation methods for interconnect opens have been proposed in [6] and [8]- [11].…”
Section: Introductionmentioning
confidence: 98%